2003
DOI: 10.1017/s0968565003000131
|View full text |Cite
|
Sign up to set email alerts
|

The asset portfolio composition of British life insurance firms, 1900–1965

Abstract: This article examines the investment practices of life assurance firms within the United Kingdom, through an analysis of the asset holdings of the sector over the period 1900 to 1965. The data are drawn from the detailed annual returns to the Board of Trade. Aggregate, sectional and individual company data are used in the study. Major trends in investment practice are identified and analysed; and cross-sectional comparisons are made. The main emphasis is on the contribution of the life assurance sector towards… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 1 publication
0
12
0
Order By: Relevance
“…Albeit with far less discretion, Keynes led a similar shift into equities at National Mutual, investing considerably more than any other insurer (Scott (2002)). Overall, the major U.K. institutions, comprising pension funds, investment trusts, and insurance companies, also largely eschewed equities in favor of fixed-income securities in this period (Hannah (1986), Burton and Corner (1968), and Baker and Collins (2003)). Keynes's portfolio was also very different from those of highly regarded U.S. investors.…”
Section: A the Case For Equitiesmentioning
confidence: 99%
“…Albeit with far less discretion, Keynes led a similar shift into equities at National Mutual, investing considerably more than any other insurer (Scott (2002)). Overall, the major U.K. institutions, comprising pension funds, investment trusts, and insurance companies, also largely eschewed equities in favor of fixed-income securities in this period (Hannah (1986), Burton and Corner (1968), and Baker and Collins (2003)). Keynes's portfolio was also very different from those of highly regarded U.S. investors.…”
Section: A the Case For Equitiesmentioning
confidence: 99%
“…In a similar fashion, major UK institutional investors such as pension funds, investment trusts, and insurance companies largely eschewed equities in favour of fixed income securities in this period (Burton and Corner, 1968;Hannah, 1986;Baker and Collins, 2003).…”
Section: The Shift Into Equitiesmentioning
confidence: 99%
“…Perhaps the most important finding of this study was the absence of any significant correlation between firm size and the proportionate holdings of ordinary shares. 46 The second study by Baker and Collins used case studies of the Midland and Westminster banks to evaluate the response of these banks to their business clients' financial distress. This study found that while the activities of these banks was consistent with the transaction bank model (the dominant paradigm in their earlier, pre-1914 study), it was also the case that in the post-Second World War period these banks were more prepared to exercise an interventionist policy, particularly for their most distressed clients.…”
Section: Accounting Banking and Financial Historymentioning
confidence: 99%